Bridging Divides: Verdi's Requiem in Post-Unification Italy. Issue 2 (2015) - Vella, Francesca
ABSTRACT: This article addresses the early Italian reception of Verdi's Messa da Requiem (1874), premièred in Milan on the first anniversary of the death of the novelist Alessandro Manzoni. Previous literature has focused on issues of musical genre and the work's political implications (particularly its connections with Manzoni and with late nineteenth-century Italian revivals of 'old' sacred music). The article examines, instead, the curiously pluralistic concerns of contemporary critics, as well as certain aspects of Verdi's vocal writing, with the aim of destabilizing traditional dichotomies such as old/new, sacred/operatic, vocal/instrumental and progress/crisis. It argues for more broad-ranging political resonances of Verdi's work, suggesting that the negotiation of a variety of boundaries both in Verdi's music and in its contemporary discussion made the Requiem dovetail with wider cultural attempts to define Italian identity.